PROFIL DAYA TAHAN OTOT, KEKUATAN OTOT, DAYA LEDAK OTOT, DAN KELENTUKAN PADA ATLET SENAM RITMIK KOTA BANDUNG MENURUT STANDAR KONI PUSAT - Dwi Putri Larasati; Ronny Lesmana; Yuni Susanti Pratiwi; Vita Murniati Tarawan Lubis (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2018)
Physical fitness is the ability of an athlete to fulfill the physical activities that are needed for the sport without becoming weary. This is a very important thing that determines an athlete’s performance. The predominant component of physical fitness for rhythmic gymnastics are muscular endurance, muscle strength, power, and flexibility. The study aimed to gather information regarding the physical fitness profile of Bandung City rhythmic gymnastic athletes before competing in Pekan Olah Raga Daerah Jawa Barat (PORDA Jabar) XI event in 2010. The descriptive studywas conducted using the survey method. Subjects consist of 9 female Bandung City rhythmic gymnastic athletes. Muscle endurance, muscle strength, power, and flexibility were measured using appropriate tests and tools and then grouped according to Standard KONI Pusat. The results of this study showed that most of the rhythmic gymnastic athletes were in this categories: perfect for arms and shoulders muscle endurance, the average for stomach muscle endurance, below standard formuscle strength of the hands, the average for muscle strength of arms and shoulders, good and very good for muscle strength of the back, the average for muscle strength of the legs, below average and average for arms and shoulders power, very good for legs power, and perfect for flexibility. In a conclusion, the performance of Bandung City rhythmic gymnastic athletes can be improved byincreasing the training that is specific for each of the physical fitness components.